Soft Skill Competency Map for the Apprenticeship Programme in the Indonesian Balikpapan Hospitality Industry - Mahfud, Tuatul; Kusuma, Bambang Jati; Mulyani, & Yogiana (Journal of Technical Education and Training, 2017)
This study aims to determine the perception of the importance of soft skill competency investment, soft skill competency need, soft skill competency learning process, and work absorption of the apprentices in Balikpapan hospitality industry. This study uses mixed method approach with sequential explanatory strategy. The first, third, and fourth objectives were achieved using a qualitative approach, while the second objective uses a quantitative approach. The qualitative data was analysed using the Interactive Model Analysis method. Meanwhile, the quantitative data were analysed using descriptive statistics method. The results revealed that the investment of soft skill competency is essential and becomes the necessary capital of a person in actualizing himself to work mainly in the implementation of the apprenticeship program. Ten priority needs of soft skill competency in F&B Production section on apprenticeship program in Balikpapan hospitality industry sector include ability to cooperate, focus in doing work, communication ability, honesty, responsibility, creativity, work initiative, discipline, politeness, and carefulness. While the top ten priorities needs on soft skill competency in the F&B Service include honesty, courtesy, communication skill, responsiveness to consumer needs, responsibility, focus in doing work, cooperation, discipline, confidence, and work initiative. The process of developing soft skill competency in the implementation of the apprenticeship program is given theoretically in the pre-apprenticeship stage and implemented at the apprenticeship activity stage in the hospitality industry. Work absorption of the apprentices reaches 72%.